Management, information and educational engineering proceedings of the International Conference on Management, Information and Educational Engineering, Xiamen, November 22-23, 2014 - Liu, Hsiang-Chuan; Sung, Wen-Pei; Yan, Wenli (CRC Press, Taylor & Francis Group, 2015)
This book contains selected Computer, Management, Information and Educational Engineering related papers from the 2014 International Conference on Management, Information and Educational Engineering (MIEE 2014) which was held in Xiamen, China on November 22-23, 2014. The conference aimed to provide a platform for researchers, engineers and academics as well as industrial professionals from all over the world to present their research results and development activities in Computer, Management, Information and Educational Engineering. The papers have been grouped under the following overarching themes: Computer Science and Information Engineering, New Technologies in Education and Sports, and Engineering Management, Production Management, Business and Economics.